Catalytic Dimerization of Bio-Based 5-methylfurfuryl Alcohol to Bis(5-methylfuran-2-yl) Methane with a Solid Acidic Nanohybrid - Jin, Duo; Fang, Chengjiang; Li, Yuanzhong; Shi, Yuanhui; Liu, Yan; Li, Hu; Yang, Song (Current Nanoscience, 2020)
Background: Liquid C8-C15 long-chain alkanes, as the main components of jet fuels or diesel, can be synthetized from abundant and renewable biomass derivatives by extending the carbon- chain length through cascade C-C coupling over acidic catalysts and hydrodeoxygenation over metal particles. Objective: This research aims to develop a carbon-increasing catalytic process through the dimerization of 5-methylfurfuryl alcohol to produce the C11 oxygenate bis(5-methylfuran-2-yl) methane. Methods: In this work, 5-methylfurfural, derivable from sugars, could be reduced to the expensive 5- methylfurfuryl alcohol over Cs2CO3 using an eco-friendly hydride polymethylhydrosiloxane. In the subsequent carbon-increasing process, a solid acidic nanocatalyst 3-chlorpyridine phosphotungstic acid (3-ClPYPW) was developed to be efficient for the conversion of 5-methylfurfuryl alcohol to bis(5-methylfuran-2-yl) methane under mild reaction conditions. Results: A good bis(5-methylfuran-2-yl) methane yield of 51.6% was obtained using dichloromethane as a solvent at a low temperature of 70°C in 11 h. The solid nanocatalyst was able to be reused for at least four cycles without a remarkable loss of catalytic activity. The kinetic study proved that the reaction is a first-order reaction with apparent activation energy (Ea) of 41.10 kJ mol-1, while the thermodynamic study certified that the reaction is non-spontaneous and endothermic. Conclusion: A novel catalytic pathway for the synthesis of BMFM (C11 oxygenate) by the one-pot process was successfully developed over solid acidic nanocatalysts 3-ClPYPW.
Keywords: fuel precursors